Modern Contraceptive Utilization and Determinant Factors among Street Reproductive-Aged Women in Amhara Regional State Zonal Towns, North West Ethiopia, 2019: Community-Based Study - Wondimnew Gashaw Kettema; Getie Lake Aynalem; Ayenew Engida Yismaw; Ayenew Worku Degu (Hindawi Limited, 2020)
Objective. Reproductive-aged women living on the street, with no doubt, are with lesser benefits of exercising their reproductive rights. Pregnancies from this marginalized population are likely to be unplanned, unwanted, and unsupported. The aim of this study, therefore, was to assess modern contraception utilization and associated factors among street reproductive-aged women in Amhara regional state zonal towns. Method. A community-based cross-sectional study was conducted among street reproductive-aged women in Amhara regional state zonal towns. A single population proportion formula was used to calculate the sample size, a similar literature-based tool adaptation was done, and a semistructured, pretested sectioned questionnaire was used. Cluster sampling technique was used to reach the study participants. Data was entered into Epi Info version 7 and exported to SPSS version 23 for analysis. A multivariable logistic regression model was fitted to control the possible effect of confounders, and finally, the independent variables were identified on the basis of OR, with 95% CI and p values less than 0.05. Results. 604 street reproductive-aged women were interviewed in the study which make the response rate 94.2%. The study revealed that current modern contraceptive utilization among the study participants was found to be 38.9%. Having history of pregnancy in street life (AOR=1.70, 1.1-2.7), having three or more live children (AOR=6.4, 2.0-20.4), undesiring to have additional children in the future (AOR=2.7, 1.4-5.1), mentioning three to four (AOR=2.2, 1.5-3.3) and five or more modern contraceptive types (AOR=5.5, 1.4-21.0), and discussion with sexual partners for contraceptive use (AOR=6.6, 4.3-10.1) were variables significantly associated with modern contraceptive utilization. Modern contraceptive utilization among the street reproductive-aged women was low. Authors suggest that awareness creation and male partner involvement in the maternal services may be important to increase contraceptive utilization.